The Influence of Promotion, Product Quality, and Price on Purchasing Decisions on the Shopee Marketplace - Made, Made; Pujiati, Herni (Dinasti Publisher, 2025)
The purpose of this study was to determine the effect of Promotion, Product Quality and Price on Purchase Decisions on the Shopee Marketplace. This research was conducted on residents of Rt 006 Rw 009 Kalisari Village, Pasar Rebo District, East Jakarta Shopee users with a total sample of 110 respondents. The research method used is a quantitative method with a descriptive design. The research was conducted by looking for primary data, through questionnaires to respondents with sampling method with saturated sampling. Data processing in this study using SPSS ver software. 24.0. The analysis technique uses instrument tests, including validity tests, reliability tests, and classical assumption tests which include normality test, heteroscedasticity test, multicollinearity test and autocorrelation test, multiple linear regression analysis and hypothesis testing using t-test to partially test hypotheses and test- F to test the hypothesis simultaneously and test the coefficient of determination. The results showed that there was a positive and significant effect of the Promotion variable on the Purchase Decision with a value of t count > t table of 2.103 < 1.98260 with a significance of < 0.05, namely 0.038 > 0.05. There is a positive and significant effect of the Product Quality variable on the Purchase Decision with a value of t count > t table that is 3.561 > 1.98260 with a significance < 0.05 of 0.001 < 0.05. There is a positive and significant influence of the price variable on purchasing decisions with a value of t count < t table of 7.832 < 1.98260 with a significance of > 0.05, namely 0.000 > 0.05. Likewise for the variables Promotion, Product Quality and Price together (simultaneously) have a positive and significant effect on Purchase Decisions, based on the results of the F test with the calculated F value > F table which is 97.822 > 2.69 and the significance <0.05 is 0.000 < 0.05.